Anti-MAdCAM Antibody Increases ß7+ T Cells and CCR9 Gene Expression in the Peripheral Blood of Patients With Crohn's Disease. (7th September 2017) - Hassan-Zahraee, Mina; Banerjee, Anindita; Cheng, John B; Zhang, Weidong; Ahmad, Alaa; Page, Karen; von Schack, David; Zhang, Baohong; Martin, Steven W; Nayak, Satyaprakash; Reddy, Padma; Xi, Li; et al.
Abstract: Objective: To define pharmacodynamic biomarkers in the peripheral blood of patients with Crohn's disease [CD] after treatment with PF-00547659, an anti-human mucosal addressin cell adhesion molecule-1 [MAdCAM-1] monoclonal antibody. Methods: In this Phase 2, randomised, double-blind, controlled study [OPERA], blood samples were analysed from patients with moderate to severe active CD who received placebo or 22.5 mg, 75 mg, or 225 mg of PF-00547659 subcutaneously at baseline and at Weeks 4 and 8, with follow-up at Week 12. Soluble MAdCAM [sMAdCAM] was measured by mass spectrometry, β7-expressing T cells by flow cytometry, and gene transcriptome by RNA sequencing. Results: A slight increase in sMAdCAM was measured in the placebo group from baseline to Week 12 [6%], compared with significant decreases in all PF-00547659 groups [–87% to –98%]. A slight increase from baseline to Week 12 was observed in frequency and molecules of equivalent soluble fluorochrome for β7+ central memory T cells in the placebo group [4%], versus statistically significant increases in the active treatment groups [48% to 81%]. Similar trends were seen for β7+ effector memory T cells [placebo, 8%; PF-00547659, 84–138%] and β7+ naïve T cells [8%; 13–50%]. CCR9 gene expression had statistically significant up-regulation [ p = 1.09e-06; false discovery rate < 0.1] with PF-00547659 treatment, and was associated with an increase in β7+ T cells. Conclusions: Results of the OPERA study demonstrate positive pharmacology and dose-dependent changes in pharmacodynamic biomarker measurements in blood, including changes in cellular composition of lymphocytes and corresponding CCR9 gene expression changes.